HUBUNGAN ANTARA SISTEM IMUN DENGAN SIKAP DAN PERILAKU MENJAGA IMUNITAS TUBUH SISWA - Siregar, Nauly Pararita; Mu’nisa, A.; Asmawati Aziz, Andi (Universitas Cokroaminoto Palopo, 2024)
This research aims to determine whether there is a relationship between students' immune system knowledge and students' attitudes and behavior in maintaining body immunity. This research uses a quantitative approach located at SMAN 3 Barru. The independent variables in this research are attitudes and behavior to maintain students' immune systems and the dependent variable in this research is students' immune system knowledge. The population in this study was Class Research data was obtained through distributing knowledge questionnaires related to students' immune systems, and attitude and behavior questionnaires related to maintaining students' immune systems. The data analysis technique used is simple regression analysis which starts from testing normality, linearity and regression. Based on the results of data analysis, the significance value for the influence of the independent variable on the dependent variable is 0.268>0.05. It can be concluded that there is no significant relationship between attitudes and behavior in maintaining body immunity and knowledge of the immune system of students at SMAN 3 Barru.